Down Girl and Sit : Smarter than Squirrels. - Nolan, Lucy (New York : marshall Cavendish, 2004)
Recounts the adventures of a rambunctious dog who thinks her name is Down Girl and her next door neighbor, Sit, as they try to keep the world safe from dangerous squirrels, the paper boy, and a frightening creature names Here Kitty Kitty.
3-6
Keywords: Dogs - Fiction; Humorous stories; Reed, Mike illus